Security Quality Measurement Framework for Academic Information System (AIS) Based on ISO/IEC 25010 Quality Model - Saptarini, Istiningdyah; Rochimah, Siti; Yuhana, Umi Laili (IPTEK Journal of Proceedings Series, 2017)
AbstractÂ¾ Academic Information System (AIS) is a CASE tool that can improve efficiency and operational effectiveness of a university. It is necessary to guarantee its security quality. In addition, AIS has different characteristics from other software. This study aims to establish a framework to measure the quality of security on the AIS application domain. The framework is built based on ISO/IEC 25010 quality model. The resulting framework showed that it can measure 20 additional security aspects and produce an aggregated security value compared to the existing quality measurement standard. It is also able to improve the quality of the case study system by an increase in security value of 15.6%.